2016
DOI: 10.1089/neu.2015.4205
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy in Traumatic Brain Injury and Its Correlation with Progressive Hemorrhagic Injury: A Systematic Review and Meta-Analysis

Abstract: The association between coagulopathy and either isolated traumatic brain injury (TBI) or progressive hemorrhagic injury (PHI) remains controversial. The aims of this study were to evaluate whether isolated TBI induces pronounced coagulopathy, in comparison with non-TBI or TBI in conjunction with other injuries (TBI + other injuries), and to examine whether there is any evidence of a relationship between coagulopathy and PHI in patients who have experienced TBI. The MEDLINE(®) and Embase databases, and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 34 publications
1
63
0
Order By: Relevance
“…5,6,9 However, very little is known about the clinical implications of DCR for patients with TBI and HS, especially considering the coagulopathy that often accompanies TBI. 1,1015 Additionally, there is virtually no data on how DCR affects neurologic status and outcomes with concomitant TBI.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,9 However, very little is known about the clinical implications of DCR for patients with TBI and HS, especially considering the coagulopathy that often accompanies TBI. 1,1015 Additionally, there is virtually no data on how DCR affects neurologic status and outcomes with concomitant TBI.…”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, post-TBI coagulation disorders are associated with progressive hemorrhagic injury (PHI) and ICH, particularly in older patients with intraparenchymal contusions. 15,18,19 Laboratory manifestations of fibrinolysis are associated with PHI, poorer outcomes, and the need for neurosurgical intervention. Furthermore, patients who displayed evidence of abnormal clot formation dynamics in their clots were approximately five times more likely to die from PHI versus patients with clot dynamics values within reference ranges.…”
Section: Coagulopathy As Prognostic Indicatormentioning
confidence: 99%
“…Most data underlying the initiation and progression of coagulopathy are speculative and not linked to causative data. The heterogeneity with respect to defining both TBI and coagulopathy presents additional challenges when attempting to study this complicated disease state 18 (►Table 1). One key factor in our understanding of this disease process may be the recognition that coagulopathy alone does not result in parenchymal bleeding without the presence of micro or macrovascular injury.…”
Section: Hemorrhagic Expansion and Mechanism Of Hemostatic Derangemenmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is controversy within the literature regarding the exact nature of hemostatic perturbations after TBI, and evidence exists for the presence of both a hypercoagulable and hypocoagulable state [2]. For example, while the initial head injury often leads to increased bleeding tendency and the exacerbation of hemorrhagic lesions [2,[46][47][48], TBI is also independently associated with an increased risk for venous thromboembolism [49][50][51][52] and ischemic stroke [53][54][55][56][57]. Autopsy studies have also revealed that micro-thrombosis is present in the majority patients who have died from head trauma [58].…”
Section: Hemostatic Disturbance In Tbimentioning
confidence: 99%